1974
DOI: 10.1073/pnas.71.3.952
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Quinones for Prophylaxis Based on a Rationale of Inhibition of Electron Transfer in Plasmodium

Abstract: Knowledge of the biochemistry of Plasmodium is emerging as a new field. Previous studies showed that the parasite apparently requires electron transfer for energy, and techniques to study such energy mechanisms are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Generally, the quinolinequinones containing a halogen at the 6-and/or 7-position exhibited slightly better tuberculostatic activity than derivatives containing a thiol group at the 6-or 7-position (compare entries 1-12 with [13][14][15][16][17][18][19]; however the precise levels of activity depended on the substitution pattern. Previous studies have revealed that chloro-ethylaminoquinolinequinones, such as 8c (entry 9), and the subsequent tricyclic compound 22 (entry 18) exhibited promise as TB-drugs.…”
Section: Tuberculostatic Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, the quinolinequinones containing a halogen at the 6-and/or 7-position exhibited slightly better tuberculostatic activity than derivatives containing a thiol group at the 6-or 7-position (compare entries 1-12 with [13][14][15][16][17][18][19]; however the precise levels of activity depended on the substitution pattern. Previous studies have revealed that chloro-ethylaminoquinolinequinones, such as 8c (entry 9), and the subsequent tricyclic compound 22 (entry 18) exhibited promise as TB-drugs.…”
Section: Tuberculostatic Activitymentioning
confidence: 99%
“…The compounds have been broadly grouped into those containing two halogen substituents (entries 1 and 2), an amine and halogen functionality (entries 3-12), those with a mono-sulfur functionality (entries [13][14][15][16][17][18][19][20][21][22][23][24], and the di-sulfur containing derivatives (entries 25-28).…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several quinolines isolated from natural sources or derivatives thereof are significant with respect to their use as antimalarials. 226 Chloroquine (203) and hydroxychloroquine (204) are among the most famous antimalarials containing the quinoline scaffold and have additionally been used to suppress the disease process in rheumatoid arthritis. As a result of their important biological activities, the development of novel strategies to access substituted quinolines has been an important focus of synthetic method development.…”
Section: Diazonamide A: Deoxygenations Of Sulfoxides N-oxides and Smentioning
confidence: 99%